TRENDS AND CHALLENGES IN ISLAMIC EDUCATION LEARNING MEDIA FOR EARLY CHILDHOOD: A SYSTEMATIC LITERATURE REVIEW - Arif, Muhamad; Chapakiya, Suraiya; Masturoh, Umi (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
The urgency of selecting effective Islamic Education learning media in the era of digital technology for early childhood education is an inevitability that cannot be postponed; a learning media based on multisensory digital technology because this media can improve understanding and retention of information, support various learning styles and are in accordance with the digital era so that it can combine audio, visual, kinesthetic, local wisdom and technology. This study aims to analyze the existence of Islamic Education learning media for early childhood, challenges and opportunities through systematic literature review research methods, the process of searching for research results using keywords in Indonesian and English, namely: Islamic Education "or" Media "or" Early Childhood, through the publish or perish eight application, some notes on the search process are the publication year range in 2015-2025 in three global databases, namely: "Google scholar, Scopus and WOS", the data analysis used is PRISMA analysis which is adjusted to the research question (RQ), 55 articles were found from the global database. The results of the study indicate that research training related to learning media can be classified into three parts, namely, integration of digital technology, integration of local wisdom, and manual media. So, the role of teachers in preparing learning media must consider the nine criteria developed by Gagne, which is abbreviated as SMART-PACK.